Conversion from cilostazol to OPC‐13015 linked to mitigation of cognitive impairment. Issue 1 (27th May 2021) - Saito, Satoshi; Shinmyozu, Kaori; Kawakami, Daisuke; Yamauchi, Miho; Ikeda, Shuhei; Hattori, Yorito; Yamamoto, Rintaro; Hayakawa, Naoki; Ihara, Masafumi
Abstract: Introduction: Cilostazol may be a novel therapeutic agent for Alzheimer's disease. Its metabolite, OPC‐13015, has a stronger inhibitory effect on type 3 phosphodiesterase than cilostazol. Methods: We prospectively enrolled patients with mild cognitive impairment to whom cilostazol was newly prescribed. Patients underwent the Montreal Cognitive Assessment (MoCA) twice, at a 6‐month interval. Plasma cilostazol, OPC‐13015, OPC‐13213, and OPC‐13217 concentrations were determined using liquid chromatography‐tandem mass spectrometry. Results: MoCA score changes from baseline to the 6‐month visit were positively correlated with ratios of OPC‐13015 to cilostazol and total metabolites ( n  = 19, P  = .005). Patients with higher ratios of OPC‐13015 (≥0.18, median value; n  = 10) had significantly higher MoCA scores ( P  = .036) than patients with lower ratios (the ratio <0.18, n  = 9). The absolute value of OPC‐13015 concentration in blood was also higher in patients with preserved cognitive function ( P  = .033). Discussion: Blood OPC‐13015 levels may be a predictive biomarker of cilostazol treatment for Alzheimer's disease.